2019
DOI: 10.1155/2019/9372505
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of Shake Table Device on Strong Earthquake Output

Abstract: In order to avoid unexpected damage of structural specimens in the test, at the beginning, a signal with small amplitude is adopted to input the shake table device to gain the transfer function and corresponding drive signal, and then a strong earthquake output can be reproduced by amplifying the drive signal proportionally. However, as there are obvious nonlinearities inherent in the shake table device and structural specimen under strong earthquakes, errors inevitably exist in the replayed and amplified eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Solutions to similar problems may be found in the literature. * e-mail: cesar.pelaez@uah.es First of all, adaptive control techniques have been extensively applied in earthquake simulations by means of shaking tables [7,8,9,10]. These adaptive techniques have also been explored in the field of humanoid robots [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Solutions to similar problems may be found in the literature. * e-mail: cesar.pelaez@uah.es First of all, adaptive control techniques have been extensively applied in earthquake simulations by means of shaking tables [7,8,9,10]. These adaptive techniques have also been explored in the field of humanoid robots [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that the CSI exert effects on the MST at the previous natural frequency of structure. Guo et al 24 analyzed the CSI effects on shaking table tests. The analysis showed that the nonlinearity of test structure has great impact on the MST and the control accuracy of the shaking table decreases.…”
Section: Introductionmentioning
confidence: 99%
“…The research on geotechnical related problems through different methods is also more and more extensive [18]. Therefore, the shaking table test has become a tool for identifying and quantifying the failure mechanism of pile foundations under the action of earthquakes [19][20][21][22]. Motamed [23] supported that mitigating the sheet pile of the floating type or fixed-end type and anchoring the quay wall to a new pile row could provide an adequate seismic performance by conducting a series of shaking table model tests.…”
Section: Introductionmentioning
confidence: 99%